Tinjauan Yuridis terhadap Bidan yang Memperdagangkan Obat Substandar dalam Perspektif Hukum Pidana dan Hukum Pidana Islam (Studi Putusan Nomor 1406/Pid.Sus/2020/PN Mdn) - Hasyim, Nafa Fadhilah; Panjaitan, Budi Sastra; Ramadani, Ramadani (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Substandard medicines trade is a very dangerous crime because it can harm society. This is the background for conducting research on Decision Number 1406/Pid.Sus/2020/Pn Mdn. The purpose of this research is to find out the review of criminal law against midwives who trade substandard medicines, to find out the review of Islamic criminal law against midwives who trade substandard medicines and to find out the judge's considerations of midwives who trade substandard medicines in decision Number 1406/Pid.Sus /2020/PN Mdn. This research is a type of normative juridical research using library research. The research approach used in this study is the case approach. The legal materials used in this study are primary legal materials in the form of court decisions and legislation, secondary legal materials in the form of law books and journals, and tertiary legal materials in the form of searches on the internet and the Big Indonesian Dictionary. In criminal law, it is prohibited to trade substandard medicines because they are considered to be detrimental and disturbing the community and will be subject to appropriate sanctions. Meanwhile in the view of Islamic criminal law, trading substandard medicines is considered a criminal act of fraud which is a Jarimah Ta'zir, namely that the criminal conviction is handed over to the judge in court. In determining sanctions against midwives who trade substandard medicines, it is more suitable to use Law Number 36 of 2009 concerning Health rather than the Criminal Code (KUHP) and Law Number 8 of 1999 concerning Consumer Protection.